2005
DOI: 10.1016/s0377-1237(05)80112-1
|View full text |Cite
|
Sign up to set email alerts
|

Local Anaesthesia for Fiberoptic Intubation : A Comparison of Three Techniques

Abstract: In conclusion the 'spray as you go' technique was safe, provided effective local anaesthesia and was preferred by both patients and endoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
3
20
1
1
Order By: Relevance
“…In our study, the intubating conditions were better in Group B compared with Group N, similar to the studies of Webb et al [ 9 ], Graham et al [ 10 ], and Sethi et al [ 15 ]. However, Reasoner et al [ 14 ] and Gupta et al [ 6 ] found no significant difference in intubating conditions between groups.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the intubating conditions were better in Group B compared with Group N, similar to the studies of Webb et al [ 9 ], Graham et al [ 10 ], and Sethi et al [ 15 ]. However, Reasoner et al [ 14 ] and Gupta et al [ 6 ] found no significant difference in intubating conditions between groups.…”
Section: Discussionsupporting
confidence: 91%
“…Adequate airway topical with minimum dosage of lignocaine is of supreme importance for patient safety .A reasonable waiting period after every spray is preferred. [27] The quality of anaesthesia was significantly better in Group A as evidenced by significantly higher patients showed procedure was not unpleasant (Grade 1 Severity score).Similar to our study Lt Col Sethi et al, [24] found that quality of laryngeal anaesthesia was significantly better in spray-as-yougo method as evidenced by lower severity scale (P<0.05) where grading of overall intubation condition was better for spray-as-you-go group (P<0.01).However Graham et al, [25] Sharma et al, [26] reported better patient comfort by transtracheal injection of local anaesthetic than spray-as-you-go method. In our study, reaction score was significantly better in group A than Group C and Group B.…”
Section: Discussionsupporting
confidence: 88%
“…Reasoner et al, [23] found no significant difference in intubation time between nerve block and topical anesthesia groups. The total dose of lignocaine including extra dose was lesser in Group A(404mg) than Group C(418mg) and Group B(436mg).However Lt Col Sethi et al, [24] found lesser amount of extra dose of lignocaine in spray-as-you-go technique but was more than transcricoid injection technique and less than nebulisation. Most authors recommend higher safe dose of topical lignocaine viz 8-9mg/kg, except in elderly or those with hepatic or cardiac impairement.…”
Section: Discussionmentioning
confidence: 89%
“…Hal ini sesuai dengan hipotesis penelitian ini yaitu kualitas intubasi yang difasilitasi oleh blok nervus superior laringeus dan transtrakeal setara dengan yang difasilitasi oleh obat pelumpuh otot yang juga sejalan dengan penelitian sebelumnya. 9,16 Penelitian ini menemukan perbedaan yang sangat signifikan (p=<0.001) pada tekanan sistolik, diastolik dan MAP dan perbedaan yang signifikan (p<0.05) pada denyut nadi sesaat setelah laringoskopi intubasi antara kedua grup. Hal ini sesuai dengan teori dimana blok superior laringeus dan transtrakeal menumpulkan sensasi nyeri yang terjadi saat manipulasi jalan nafas seperti laringoskopi intubasi endotrakeal sehingga tidak terjadi stimulasi simpatis yang dapat menimbulkan respons hemodinamik berupa peningkatan tekanan darah dan denyut nadi.…”
Section: Respons Hemodinamikunclassified